Organizational hybridity : perspectives, processes, promises - Besharov, Marya; Mitzinneck, Bjoern (Bingley, U.K. : Emerald Publishing Limited, 2020)
This book contains Open Access chapters. As complex, intractable social problems continue to intensify, organizations respond with novel approaches that bridge multiple institutional spheres and combine forms, identities, and logics that would conventionally not go together, creating hybridity. Scholarly research on this phenomenon has expanded in tandem, drawing on varied theoretical lenses and exploring a widening array of empirical contexts.This edited volume takes stock of recent developments in the literature and sets a foundation for the next generation of research on organizational hybridity. It offers a multi-level, dynamic approach for capturing and explaining heterogeneity in how hybridity manifests and evolves within organizations and fields over time. The chapters included in the volume cover institutional logics, organizational identity, social categories, and paradox approaches to hybridity, and they examine settings ranging from social enterprise, microfinance, and impact investing to business sustainability, health care, and government. Taken as a whole, the volume provides both inspiration and analytical tools for developing timely and relevant insights to address pressing societal challenges. It is essential reading for organizational scholars, as well as leaders in business, non-profit, and public sector organizations.
Prelims -- Chapter 1: Heterogeneity in organizational hybridity: a configurational, situated, and dynamic approach -- Section A: Multiple theoretical lenses -- Chapter 2: Hybridity and institutional logics -- Chapter 3: Taking hybridity for granted: institutionalization and hybrid identification -- Chapter 4: Reasoning with heuristics: a new approach to categories theory and the evaluation of hybrids -- Chapter 5: A paradoxical approach to hybridity: integrating dynamic equilibrium and disequilibrium perspectives -- Section B: Varied empirical contexts -- Chapter 6: Business sustainability as a context for studying hybridity -- Chapter 7: How the zebra got its stripes: individual founder imprinting and hybrid social ventures -- Chapter 8: New hybrid forms and their liability of novelty -- Chapter 9: Let's talk about problems: advancing research on hybrid organizing, social enterprises, and institutional context -- Section C: Multilevel and dynamic approaches -- Chapter 10: Shift in hybridity in response to environmental complexity: the transformation of the Italian Guardia di Finanza -- Chapter 11: Hybrid agency: sheltered workshops (19412019) -- Chapter 12: Institutional settlements and organizational hybridity: the rise and fall of supervised consumption sites -- Chapter 13: Legitimacy trade-offs in hybrid fields: an illustration through microfinance, impact investing and social entrepreneurship -- Index.
Includes index.
Print version record.
Keywords: Organizational sociology; Social Science -- Sociology / Social Theory; Sociology